On the S-asymptotically ω-periodic mild solutions for multi-term time fractional measure differential equations - Gou, Haide (Topological Methods in Nonlinear Analysis, 2023)
In this paper, based on regulated functions and fixed point theorem, a class of nonlocal problem of multi-term time-fractional measure differential equations involving nonlocal conditions in Banach spaces. Firstly, we introduce the concept of S-asymptotically ω-periodic mild solution, on the premise of by utilizing (β,γ_k)-resolvent family and measure functional (Henstock-Lebesgue-Stieltjes integral), the existence of S -asymptotically ω periodic mild solutions for the mentioned system are obtained. Finally, as the application of abstract results, the existence S-asymptotically ω-periodic mild solution for a classes of measure driven differential equation are discussed.